The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/bg-10-1365-2013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of four decades of annual nitrogen addition on dissolved organic matter in a boreal forest soil

Abstract: Addition of mineral nitrogen (N) can alter the concentration and quality of dissolved organic matter (DOM) in forest soils. The aim of this study was to assess the effect of long-term mineral N addition on soil solution concentration of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) in Stråsan experimental forest (Norway spruce) in central Sweden. N was added yearly at two levels of intensity and duration: the N1 treatment represented a lower intensity but a longer duration (43 yr) of N ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…As SUVA is a common indicator of DOM aromaticity, this result suggests that the long-term N addition shifted soil DOM to a higher relative abundance of aromatics in the deeper soil horizons. Short-term N additions in different forests have shown distinct responses of SUVA to N addition. , However, the present results coincide with an earlier finding that 4 decades of N addition increased the SUVA of soil-derived DOM in B horizons but not in O horizons in a boreal forest and another finding that SUVA and soluble phenols in soil DOM at 75 cm were all increased at four different forests with 10 years of N addition . Furthermore, the average E2/E3 ratios were consistently lower in the N-added soils than those in control soils in all horizons (Figure ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As SUVA is a common indicator of DOM aromaticity, this result suggests that the long-term N addition shifted soil DOM to a higher relative abundance of aromatics in the deeper soil horizons. Short-term N additions in different forests have shown distinct responses of SUVA to N addition. , However, the present results coincide with an earlier finding that 4 decades of N addition increased the SUVA of soil-derived DOM in B horizons but not in O horizons in a boreal forest and another finding that SUVA and soluble phenols in soil DOM at 75 cm were all increased at four different forests with 10 years of N addition . Furthermore, the average E2/E3 ratios were consistently lower in the N-added soils than those in control soils in all horizons (Figure ).…”
Section: Resultssupporting
confidence: 88%
“…While several studies have hypothesized that DOM may respond differentially to the long-term addition, ,,, this study identified previously unreported shifts in DOM composition with long-term N addition. After 22 years of N addition, soil-derived DOM exhibited a minor increase in its storage (an increase of ∼10%) but had significant alterations in its optical properties and molecular-level composition.…”
Section: Resultsmentioning
confidence: 66%
“…There are studies that found increased DOC concentrations (Pregitzer et al, 2004;Fröberg et al, 2013;Shi et al, 2019). However, other field studies did not find effects on DOC from N applications (Magill et al, 2004;McDowell et al, 2004;Rappe-George et al, 2013). In fact the conventional concept for forest fertilization is to repeat application after around seven years which corresponded well to the duration of fertilization effects seen in this study.…”
Section: Discussionsupporting
confidence: 75%
“…Under most conditions, the addition of N did not change the overall pattern of monthly changes in soil DOC and DIC as compared to the control. In many studies only minor or no effects of addition N have been found 35,36 . We found that the soil DOC changes significantly and rapidly between months.…”
Section: Discussionmentioning
confidence: 99%